REGULASI DAN KONSEKWENSI HUKUM TERHADAP WALI DALAM PENGELOLAAN HARTA ANAK DI BAWAH UMUR - A Hamid (Prodi Ilmu Hukum, Universitas Teuku Umar, 2019)
The purpose of this study is to determine how the low regulation to quardianship in managing the child's legacy under his guardianship, how's the law consequence against the guardianship of children underage who are not based on a court decision. The impact of this problems is also there needs to a special handling and sustainable on the rights of children that have been orphan because of loss father and mother, cause of they are still underage, so it is needed the management system of their parents legacy (if there is). This research using Library Research and Field Research namely, to seek secondary data by studying the variety of literature in the form of books, legislation, papers, articles, journals and another documents relating to this research. Also using the method of approach to the problem by looking at the norms / provisions of applicable law , then are connected with the facts that there from the problems will be researched.The results of of research found that, After tsunami disaster in Aceh, majority of the guardianship system that occurred in every village at Peukan Bada subdistrict were not the result of formal appointment based on the decision of Syar'iyah Court, but based on mutual agreement within the family or community with didn't regard to the orphans did them have a treasure or did not, anything like this are customary provisions that apply in the society. Keywords: Law, Treasure, Underage child, guardianship.